Chapter 手塚治虫とグルメマンガをつなぐもの-「あしたのジョー」の減量 / The one which connects a gourmet cartoon with Osamu Tezuka: Cutting of Joe of tomorrow - Yamada, Natsuki (Studi e saggi, 2021)
I talk on change in the nature of the character in the cartoon through description of a food and the genre called a gourmet cartoon again. Specifically, the process until the character will be the existence which 'mediates between a story with a reader' is analyzed so that it may be seen in the gourmet cartoon. First I pay attention to Tezuka Osamu early stage work, Takamori Asao original work and Chiba Tetsuya taking pictures "Joe of tomorrow". And it is considered about the thing description about life and death there foreground propizes through a food. Further, it is confirmed that the effort and the growth drawn closely in "Joe of tomorrow" are formalized since putting it in the after work. It is inspected that the autonomy of the character becomes self-evident by this thing. And it is also inspected that the genre as the gourmet cartoon is formed consequently.